Zebrafish Plzf transcription factors enhance early type I IFN response induced by two non-enveloped RNA viruses. (April 2016) - Aleksejeva, E.; Houel, A.; Briolat, V.; Levraud, J.-P.; Langevin, C.; Boudinot, P.
Abstract: The BTB-POZ transcription factor Promyelocytic Leukemia Zinc Finger (PLZF, or ZBTB16) has been recently identified as a major factor regulating the induction of a subset of Interferon stimulated genes in human and mouse. We show that the two co-orthologues of PLZF found in zebrafish show distinct expression patterns, especially in larvae. Although zbtb16a/plzfa and zbtb16b/plzfb are not modulated by IFN produced during viral infection, their over-expression increases the level of the early type I IFN response, at a critical phase in the race between the virus and the host response. The effect of Plzfb on IFN induction was also detectable after cell infection by different non-enveloped RNA viruses, but not after infection by the rhabdovirus SVCV. Our findings indicate that plzf implication in the regulation of type I IFN responses is conserved across vertebrates, but at multiple levels of the pathway and through different mechanisms. Highlights: PLZF (Promyelocytic Leukemia Zinc Finger) is a BTB-POZ transcription factor. Two co-orthologs of the human PLZF are found in teleost fish species. Zebrafish Plzf enhance the type I IFN response induced by poly I:C or RNA viruses. Zebrafish Plzf proteins affect the early type I IFN response.